2022
DOI: 10.1016/j.biopsych.2021.12.017
|View full text |Cite
|
Sign up to set email alerts
|

PDZD8 Disruption Causes Cognitive Impairment in Humans, Mice, and Fruit Flies

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…In contrast to the detrimental effects of increased tethering, reducing MERCs by knockdown of pdzd8 in Drosophila neurons dramatically delayed age-associated decline in locomotor activity and significantly extended median lifespan compared with control animals. Our results corroborate a recent study showing that adult Pdzd8 -deficient mice display increased locomotor activity compared with control littermates ( Al-Amri et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the detrimental effects of increased tethering, reducing MERCs by knockdown of pdzd8 in Drosophila neurons dramatically delayed age-associated decline in locomotor activity and significantly extended median lifespan compared with control animals. Our results corroborate a recent study showing that adult Pdzd8 -deficient mice display increased locomotor activity compared with control littermates ( Al-Amri et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…The importance of the mitochondria-ER platform is particularly evident in neural cells. Astrocytic MERCSs facilitate vascular remodelling [21], and loss of PDZD8 (a molecular tethering protein that supports ERmitochondria contacts) disrupts neuronal cellular calcium dynamics [22] and synaptic plasticity [23]. In humans, recessive loss-of-function PDZD8 variants cause neurodevelopmental cognitive impairment [23].…”
Section: Mitochondrial Contact Sitesmentioning
confidence: 99%
“…The direction of this correlation is also confirmed in the study, which showed the absence of irradiation effects on habituation against the background of anxiolytic therapy [ 82 ]. On the other hand, in both humans and animals, the disruption of habituation is strongly correlated with cognitive impairments [ 94 , 95 ] and vice versa [ 93 , 96 ]. Thus, both active OEB and rapid habituation of irradiated rodents indirectly indicate a possible enhancement of cognitive abilities.…”
Section: Mental Health and Ionizing Radiationmentioning
confidence: 99%